Fiscal Consolidation in Israel : A Global Fiscal Model Perspective - Epstein, Natan (IMF Working Papers; Working Paper, 2006)
Fiscal consolidation has become an important policy prescription for many emerging market countries (EMCs), particularly for the highly indebted ones. Although prudent fiscal policies tend to reduce vulnerabilities, their implementation is usually postponed. This paper represents, to the best of our knowledge, one of the first attempts in the literature to quantify the costs of delaying fiscal consolidation in an EMC. In particular, using the IMF's Global Fiscal Model (GFM), we find that early consolidation through expenditure cuts would result in a substantial increase in Israel's long-term output growth relative to the case with delayed fiscal adjustment. Using an alternative fiscal instrument, we find that delaying tax cuts would result in cumulative real GDP that is much larger than otherwise.